Мемуары Анны Евдокимовны Лабзиной – документ познания нравственности русской женщины в конце XVIII века - Waliszewska, Grażyna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Anna Labzina, born in the eighteenth century in a gentry family, left extraordinary memoirs. Her diaries are not a testimony of time but rather reflect her very own experiences and emotions connected with her unsuccessful marriage, a decision which was made when she was thirteen years old. Her notes confirm the eighteenth-century principle of absolute dependence on one’s husband. Labzina accepts and suffers dependence meekly, but from her words the picture of a “pained soul” emanates – the only thing she can rebel against is her fate.
Anna Evdokimovna Labzina’s memoirs – a contribution to recognizing Russian women’s customs in the 18th century
Memuary Anny Jewdokimowny Łabziny – przyczynek do poznania obyczajowości kobiety rosyjskiej końca XVIII wieku